The Fourth Industrial Revolution: Issues and Implications for Career Research and Practice - Hirschi, Andreas (The Career development quarterly, 2018)
The accelerating digitization and automation of work, known as the 4th industrial revolution, will have an enormous impact on individuals’ career experiences. Yet, the academic literature in vocational psychology and career research has been remarkably silent on this trend so far. This article summarizes some of the most important issues of the 4th industrial revolution as they pertain to career development. The author then critically reviews how current models and frameworks of career development are suitable for addressing these emerging issues. Opportunities for future career development research and practice are outlined.